Establishment and Implementation of the Point-of-Care RT-RAA-CRISPR/Cas13a Diagnostic Test for Foot-And-Mouth Disease Virus Serotype O in Pigs - Ping Meng; Bo Ni; Chenyu Li; Zhou Sha; Chunju Liu; Weijie Ren; Rong Wei; Fuxiao Liu; Jinming Li; Zhiliang Wang (Viruses)
Foot and mouth disease virus (FMDV) is a highly pathogenic virus that mainly infects cloven hooved animals, such as pigs. The establishment of a rapid, sensitive and accurate point-of-care detection method is critical for the timely identification and elimination of infected pigs for controlling this disease. In this study, a RT-RAA-CRISPR/Cas13a method was developed for the detection of FMDV serotype O in pigs. Six pairs of RT-RAA primers were designed based on the conserved gene sequence of FMDV serotype O, and the optimal amplification primers and reaction temperatures were screened. The CRISPR-derived RNA (crRNA) was further designed based on the optimal target band sequence and the most efficient crRNA was screened. The results revealed that FMDV-O-F4/R4 was the optimal primer set, and the optimal temperature for the RT-RAA reaction was 37 °C. Moreover, crRNA4 exhibited the strongest detection signal among the six crRNAs. The established RT-RAA-CRISPR/Cas13a method demonstrated high specificity and no cross-reactivity with other common swine pathogens such as Senecavirus A (SVA), porcine reproductive and respiratory virus (PRRSV), porcine epidemic diarrhea virus (PEDV), porcine circovirus type 2 (PCV2), classical swine fever virus (CSFV), and pseudorabies virus (PRV), additionally, it was observed to be highly sensitive, with a detection limit of 19.1 copies/µL. The repeatability of this method was also observed to be good. This method could produce stable fluorescence and exhibited good repeatability when three independent experiments yielded the same results. A validation test using three types of simulated clinical samples (including swab, tissue, and serum samples) revealed a 100% concordance rate. The detection results could be visualized via a fluorescence reader or lateral flow strips (LFSs). Thus, a highly specific and sensitive RT-RAA-CRISPR/Cas13a detection method was developed and is expected to be applied for the rapid detection of FMDV serotype O in situ.